Structural, electronic, magnetic, optical and thermoelectric properties of ferromagnetic double perovskites K2ScCoX6 (X = F, Cl): A first-principles study - Vineet Tirth; Amina; Muhammad Kamran; Salhah Hamed Alrefaee; A.M. Quraishi; Dilsora Abduvalieva; Albandary Almahri; Naseem Akhter; Noureddine Elboughdiri; Rawaa M. Mohammed; Ali Algahtani; Hassan Alqahtani; et al. (Case Studies in Thermal Engineering, 2024)
To identify a promising alternative to lead-based materials for solar cell application, we investigated the different physical properties of K2ScCoX6 (X = F, Cl) perovskites. Both materials have ferromagnetic ground state. The obtained optimize lattice constants are found to be 8.48 Å and 10.04 Å for K2ScCoF6 and K2ScCoCl6 respectively. Our finding indicate that these materials exhibit excellent structural, mechanical, the thermal stability, as evidenced by their Goldsmith's tolerance factor, elastic parameters, and negative formation energies. The formation energy is found to be -2.4 and -2.1 eV/atom for K2ScCoF6 and K2ScCoCl6 respectively. The electronic properties reveals that both materials have semiconducting nature. Notably, we observed low direct bandgap of 0.93 eV for K2ScCoF6 and 1.22 eV for K2ScCoCl6, which contrast with the typically large bandgap values reported for most halide double perovskite. The calculated values of Poisson's and Pugh's ratios, along with positive Cauchy's pressure, suggest a ductile nature for these compounds. Additionally, the optical properties show high absorption and optical conductivity, coupled with low reflectivity and minimal energy loss in lower energy ranges. These results suggest that the halogen-based double perovskite materials have significant potential as photovoltaic absorber materials in solar cell applications. Furthermore, their higher Seebeck coefficients, power factors and low thermal conductivity at room temperature underscore their potential for thermoelectric applications.